Capsaicin-induced secondary hyperalgesia differences between the trigeminal and spinal innervation - Isabela C. Novaes; Soraya S. Ardestani; Allen Matheus S. Nascimento; Paulo C. R. Conti; Leonardo R. Bonjardim; Peter Svensson; Fernando G. Exposto; Yuri M. Costa (Scientific Reports)
Abstract This study compared the degree of secondary hyperalgesia and somatosensory threshold changes induced by topical capsaicin between spinal and trigeminal innervation. This crossover clinical trial included 40 healthy individuals in which 0.25 g of 1% capsaicin cream was randomly applied for 45 minutes to a circular area of 2 cm2 to the skin covering the masseter muscle and forearm in 2 different sessions, separated by at least 24 hours and no more than 72 hours (washout period). The main outcome variables were the area of allodynia and pinprick hyperalgesia, as well as electrical and mechanical pain thresholds within the area of pinprick hyperalgesia. Mixed ANOVA models and McNemar tests were applied to the data (p = 0.050). The occurrence of allodynia and pinprick hyperalgesia was higher in the forearm than in the masseter (p < 0.050). Additionally, the areas of pinprick hyperalgesia and allodynia were larger in the forearm compared to the masseter (p < 0.050). The electrical and mechanical pain thresholds demonstrated a loss of somatosensory function following capsaicin application to the masseter (p < 0.050). However, no significant somatosensory threshold changes were observed at the forearm after capsaicin (p > 0.050). In conclusion, these findings indicate potential differences compatible with central sensitization related to secondary hyperalgesia between trigeminal and spinal innervation.